A Study on Volume, Speed and Lane Distribution of Mixed Traffic Flow by using Video Graphic Technique - Prakash Koganti, Shyam; Hemantha Raja, Kommineni; Sajja, Satish; Sai Narendra, M (International Journal of Engineering and Technology, 2018)
Lane Distribution Factor (LDF) is an integral part of load calculations on urban and rural highways. LDF describes the distribution of vehicular traffic across the roadway. It depends on the traffic composition, speed and volume, origin destination patterns of drivers etc. LDF is developed for transportation planners and highway engineers based on an estimation of macro level utilization of each lane by the total traffic volume. The above information is absolutely necessary to understand the fatigue behaviour of the pavements through number of probable applications of wheel loads on a portion of the pavement which also decides the required thickness. Accordingly, the IRC: 37 - 2012 suggested a set of Lane Distribution Factor for use in the design of flexible pavements. A Two lane road and an Intermediate lane road in urban environment are evaluated using Video Graphic technique. Analysis is carried out for the collected data and the results are also presented in detail for each category of vehicles. Lane distribution factors and Directional distribution factors are developed for both Two lane and Intermediate lane roads.Â Â